Raymonda - Glazunov, Aleksandr Konstantinovich 1865-1936 (Opéra national de Paris, 2009)
Raymonda is an emotional three-act ballet with music by Alexandre Glazunov. Premiered at the Mariinsky Theater in 1898 featuring choreography by Marius Petipa, the ballet is performed here with Rudolf Nureyev's adapted choreography for his 2008 production at the Opéra de Paris, starring the great Marie-Agnès Gillot, José Martinez, and Nicolas Le Riche. Rudolf Nureyev's 1964 Spoleto Festival production of Raymonda was the first great ballet the choreographer had mounted in Europe. After three adaptations, he presented his definitive choreography of the ballet at the opening of the 1983-1984 at the Opéra national de Paris, when he officially took on his there new role as Director of Dance. The work tells the story of Raymonda, whose fiancé Jean de Brienne has left on a crusade. A strange and sensual "enemy" soon appears to her in a dream: the Saracen Abderam
Keywords: Ballets; Filmed ballets; Internet videos